The effect of ramadan fasting in maintaining blood sugar and cholesterol stability in diabetes mellitus patients 2 - Oksita Asri Widyayanti; Fida Dyah Puspasari (Institute of Computer Science (IOCS), 2026)
Introduction: Fasting is a practice of abstaining from food and drink for 11–18 hours each day over a full month and is known to have benefits in controlling blood glucose and cholesterol levels. Type 2 diabetes mellitus (T2DM) is characterized by hyperglycemia and metabolic disorders that may increase the risk of complications, including those related to hypercholesterolemia. Ramadan fasting has the potential to provide positive effects on metabolic control in patients with T2DM. Objective: This study aimed to determine the effect of Ramadan fasting on random blood glucose (RBG), fasting blood glucose (FBG), and cholesterol levels in patients with T2DM in Jompo Kulon Village. Methods: This study employed a quasi-experimental design with a Pretest–Posttest Control Group. Samples were obtained using a purposive sampling technique and consisted of patients with T2DM in Jompo Kulon Village. Result: The study was conducted during the month of Ramadan in 2025. Data analysis was performed using the Paired T-Test and Mann–Whitney Test. The results showed a decrease in RBG, FBG, and cholesterol levels in the fasting group compared to the control group, with a p-value > 0.001. Conclusion: It can be concluded that Ramadan fasting can reduce RBG, FBG, and cholesterol levels in patients with T2DM compared to those who do not fast.